Implication of milling methods, thermal treatment, and particle size of feed in layers on mineral digestibility and retention of minerals in egg contents. (28th January 2015) - Hafeez, A.; Mader, A.; Ruhnke, I.; Röhe, I.; Boroojeni, F. Goodarzi; Yousaf, M. S.; Männer, K.; Zentek, J.
Abstract : Feed production with different milling methods, thermal treatment, and particle size may influence mineral digestibility and retention in eggs. The present study investigated the impact of roller (R) and hammer (H) mills, mash (M) and expandate (E) with fine (F) and coarse (C) particle sizes, on apparent ileal absorption (AIA) and apparent total digestibility (ATD) and retention of calcium, phosphorus, magnesium, zinc, manganese, copper and iron in yolk, albumen, and shell. A total of 384 hens (Lohmann Brown), 19 weeks old, were assigned using a randomized design with a 2 × 2 × 2 factorial arrangement. Eight experimental diets were offered ad libitum during the whole experimental period and one week before for diet adaption. The AIA of magnesium, zinc, copper, and iron was higher in treatment R in comparison with treatment H ( P < 0.01, P ≤ 0.03, P < 0.01 and P < 0.01, respectively). The AIA of magnesium was higher in treatment M than treatment E ( P < 0.01). The AIA of magnesium was higher in treatment C in comparison with treatment F ( P ≤ 0.05) due to particle size. The ATD of copper and iron was higher in treatment R than treatment H ( P < 0.01 and P ≤ 0.03, respectively). The ATD was higher for phosphorus and lower for iron in treatment F than treatment C ( P ≤ 0.05 and P ≤ 0.02. respectively). The copper concentration in yolk and albumen was higher in treatment C than treatment F ( P < 0.01 and P ≤ 0.03, respectively). Besides a few overall interactions, the AIA and ATD of copper and manganese were lower in H+M group than R+M group ( P ≤ 0.05). The ATD of iron was higher in the M+C group compared to the M+F group ( P < 0.01), whereas the albumen zinc concentration was higher in the E+C group than E+F group ( P < 0.01). In conclusion, the feed produced by hammer mill had negative effects on AIA and ATD for trace elements in particular, but mineral concentrations in egg contents were mostly comparable for all treatments. Therefore, milling methods, thermal treatment, and particle sizes used in the present study can be used for layer feed formulation without negatively affecting egg quality.